Intra abdominal adhesion after ovariosalpingohisterectomy in a bitch-Case report - De Freitas, Silvio Henrique [UNESP]; Dória, Renata Gebara Sampaio; Laskoski, Luciane Maria; Gomes, Ana Helena Benetti; De Souza Mendonça Dr., Fábio; Pires, Marco Aurélio Molina; De Camargo Dr., Lázaro Manoel (My University, 2012)
A case of adhesion of small intestine, ureters, bladder and uterine stump after ovariosalpingohisterectomy as a result of uterus ligature with the use of silk suture was reported. The animal presented partial obstruction of the small intestine due to a foreign body placed cranially to the adhesion. After adhesiolysis of the ureters and surgical partial resection of the small intestine, bladder and uterine stump the patient returned to its normal activities.
Aderência intra-abdominal após ovariosalpingohisterectomia em cadela - Relato de caso
Keywords: Bladder; Silk suture; Small intestine; Ureters; Uterus